Fine tuning of on-growing diets for farmed marine fish species as a key tool to sustain the aquaculture development - Mongile, Fulvio <1986> (Alma Mater Studiorum - Università di Bologna, 2014)
The aim of this thesis was to investigate some important key factors able to promote the prospected growth of the aquaculture sector. The limited availability of fishmeal and fish oil led the attention of the aquafeed industry to reduce the dependency on marine raw materials in favor of vegetable ingredients. In Chapter 2, we reported the effects of fishmeal replacement by a mixture of plant proteins in turbot (Psetta maxima L.) juveniles. At the end of the trial, it was found that over the 15% plant protein inclusion can cause stress and exert negative effects on growth performance and welfare. Climate change aroused the attention of the aquafeed industry toward the production of specific diets capable to counteract high temperatures. In Chapter 3, we investigated the most suitable dietary lipid level for gilthead seabream (Sparus aurata L.) reared at Mediterranean summer temperature. In this trial, it was highlighted that 18% dietary lipid allows a protein sparing effect, thus making the farming of this species economically and environmentally more sustainable. The introduction of new farmed fish species makes necessary the development of new species-specific diets. In Chapter 4, we assessed growth response and feed utilization of common sole (Solea solea L.) juveniles fed graded dietary lipid levels. At the end of the trial, it was found that increasing dietary lipids over 8% led to a substantial decline in growth performance and feed utilization indices. In Chapter 5, we investigated the suitability of mussel meal as alternative ingredient in diets for common sole juveniles. Mussel meal proved to be a very effective alternative ingredient for enhancing growth performance, feed palatability and feed utilization in sole irrespectively to the tested inclusion levels. This thesis highlighted the importance of formulating more specific diets in order to support the aquaculture growth in a sustainable way.